Association analysis of a novel SNP in GPR54 gene with reproductive traits in Indian goats - Ahlawat, Sonika (Indian Journal of Dairy Science, 2014)
G - protein-coupled receptor (GPR54) acts as a cognate receptor for a family of neuropeptides called kisspeptins, which are the peptide products of KiSS1 gene. KiSS1/GPR54 system is considered fundamental gatekeeper of puberty onset in mammals. Hence, it is possible that the polymorphisms of these genes have some relationship with reproductive traits such as prolificacy, sexual precocity and year-round estrus phenotypes of goats. The aim of the present work was to genotype Black Bengal goats for the mutation C1122T identified in exon 1 of GPR54 gene in order to analyze association with reproductive traits. As far as sexual precocity trait is concerned, the CC genotype individuals attained sexual maturity earlier than the CT individuals but this difference was not statistically significant. Similarly, the effect of season of kidding, year of kidding, parity and genotype on litter size was also not significant. However regression of age at sexual maturity on litter size was significant (Pâ‰¤0.05). These results preliminarily indicated that the GPR54 gene may have some association with reproductive traits in goats